Digital saving machine / Nuraliah Yahya ... [et al.] - Yahya, Nuraliah; Abd Razak, Naimah A’milin; Mohd Khazairi, Nur Izzatul Akma; Dzulkarnain Goh, Nurul Ain Amiesya; Zaini, Nur Hidayah (Universiti Teknologi MARA, Kedah, 2023)
Saving is an important and essential aspect for everyone to have a secure financial future. Saving money requires discipline of setting aside money in one special place and it requires patience and vision of what that money is for. With Digital Saving Machine, your saving experiences will have less limitations and helps users to have discipline in saving money. The machine is built with a touch screen with its built in app for people to customize their saving folder. This machine is used for saving money to reach certain goals. The objectives of this machine are to attract people making their own savings, let people have the convenience of saving personally, and help users to have discipline in managing money. We added some new elements such as digital systems similar to ATM or CDM machines so that users can easily estimate their savings amount. Furthermore, this system will also warn the user if there is an error or withdrawal before reaching the target. The final result will be determined automatically, and a system-wide indicator for performance level will appear. It also provides users with features that enable them to save their personal money at home without worrying about safety. This is because they have a very strict system which is provided with face recognition and a pin to be set up. Thus, this helps to minimize time taking, make people trust the system and increase people to make saving for their own at home. In conclusion, this machine could help many users out there to be more disciplined in saving and managing money in the future. With its strict system, guaranteed safety and automatic counting money features, this innovative piggy bank will definitely exceed the rivals in terms of quality and usefulness.